Consequences and Considerations of "Free Speech" in Higher Education: Validating Trans and Nonbinary Identities in the Classroom Setting - Moore, Bryan C.; Osborn, Max; DeJong, Christina (Journal of criminal justice education, 2025)
In several recent legal cases, college and university professors have argued that refusing to honor transgender students' chosen names and/or pronouns is protected by the "right to free speech." This raises several interesting questions. First, does an educator have an obligation to respect an individual's chosen pronouns or name? Second, even if there is no such legal obligation, why is it in the best interest for the educator to honor the chosen pronouns and name of a student? Third, how can educators be more aware of trans issues in the classroom and proactively introduce ways to respect trans identities? Our article concludes with a discussion of best practices to facilitate an inclusive learning environment that promotes learning and mutual respect.